Doing Criminology and Criminal Justice in Ireland: Perspectives From a Peripheral Nation - Marder, Ian D. (Journal of contemporary criminal justice, 2023)
This special issue invites authors engaged in cutting-edge research on crime and criminal justice in the Republic of Ireland to demonstrate Ireland’s global significance in these fields. Irish criminology is a burgeoning, diverse and outward-looking discipline, with a rising number of scholars making novel contributions to international debates on the theoretical and empirical study of crime and criminal justice. Its relatively unique position as both a Western European democracy and a post-colonial territory means that Ireland is of equal significance to the Global North and Global South. Moreover, this growth in local scholarship coincides with changes to criminal justice that should be of interest to advocates and analysts around the world. With articles on gendered historical abuses, public attitudes to policing, countering violent extremism, penal decision-making, penal politics, youth justice and organised crime, the issue brings this research to a global audience.